Intrusion detection security system with IOT sensors - Chean, Vernon Lynn Chii (2021)
This project is an IoT sensor-based security project that detect intrusion for indoor area. Usually, security systems were installed at outdoor area which vulnerable to physical attack as the systems are visible. However, if the system was installed indoor, the system will be protected and prevent from physical damage. The intrusion detection security system is using the IoT sensors to detect the surrounding especially there is abnormal activities happened in the indoor area. However, IoT sensors do not recognise the abnormal activities, when the magnetic sensor of the door is disconnected, the door is opened; when the IR sensor detect blockage, there is something pass by. The sensors do not know what object is passed by, is it a person or others object. Therefore, object detection is introduced in the project as a guidance. Object detection using the camera to scan the area and know whether that is a person or not. This can reduce the false alarm that trigger by the system hence increase the creditability of the system.